Manipulation of morphology and structure of the top of GaAs nanowires grown by molecular-beam epitaxy *Project supported partly by the MOST of China (No. 2015CB921503), the National Natural Science Foundation of China (Nos. 61504133, 61334006, 61404127), and Youth Innovation Promotion Association, CAS (No. 2017156). (October 2017) - Li, Lixia; Pan, Dong; Yu, Xuezhe; So, Hyok; Zhao, Jianhua
Abstract: Self-catalyzed GaAs nanowires (NWs) are grown on Si (111) substrates by molecular-beam epitaxy. The effect of different closing sequences of the Ga and As cell shutters on the morphology and structural phase of GaAs NWs is investigated. For the sequences of closing the Ga and As cell shutters simultaneously or closing the As cell shutter 1 min after closing the Ga cell shutter, the NWs grow vertically to the substrate surface. In contrast, when the As cell shutter is closed first, maintaining the Ga flux is found to be critical for the following growth of GaAs NWs, which can change the growth direction from [111] to 〈 11 1 ¯ 〉 . The evolution of the morphology and structural phase transition at the tips of these GaAs NWs confirm that the triple-phase-line shift mode is at work even for the growth with different cell shutter closing sequences. Our work will provide new insights for better understanding of the growth mechanism and realizing of the morphology and structure control of the GaAs NWs.